Transient thermal analysis of a lithium-ion battery pack comparing different cooling solutions for automotive applications. (15th November 2017) - De Vita, Armando; Maheshwari, Arpit; Destro, Matteo; Santarelli, Massimo; Carello, Massimiliana
Highlights: An experimental set-up is designed and developed for thermal characterization of a Li-ion battery. Heat generation and internal resistance profile at various C-rates (1C, 2C, 5C and 8C) are studied. Heat entropic coefficient and internal resistance determination with temperature dependence were performed. A battery thermal model is developed and used in a CFD-3D software for cooling methods analysis. Abstract: This paper presents a computational modeling approach to characterize the internal temperature distribution within a Li-Ion battery pack. In the mathematical formulation both entropy-based and irreversible-based heat generation have been considered; combined with CFD software in order to simulate the temperature distribution and evolution in a battery pack. A prismatic Li-ion phosphate battery is tested under constant current discharge/charge rates of 1C, 2C, 5C and 8C. Model parameters (in particular, the entropic heat coefficient and the internal resistance) needed for the calibration of the model are determined using experimentation. The model is then used to simulate two different strategies for the thermal control of a battery pack in case of car application: an air-cooling and a liquid-cooling strategy. The simulation has highlighted the pros and cons of the two strategies, allowing a good understanding of the needs during the process of battery pack design and production.